Proses Penyidikan oleh Kepolisian terhadap Orang Dengan Gangguan Jiwa yang Melakukan Kejahatan - Yuli Hermawan (Kajian Hasil Penelitian Hukum, 2019)
The purpose of this study is to find out how the mechanism of the investigation process by the police against people with mental disorders who commit crimes. Because it takes maximum effort and cooperation between various parties in handling people with mental disorders who commit crimes, so that the right decision can be made to provide action against the perpetrators. The results of this study indicate that the process of investigation by the police against people with mental disorders who have committed crimes often experiences many obstacles and obstacles so that the legal certainty is unclear.